(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
A minkowski fractal antenna is designed with a dimensions of substrate (27x27x1.6)mm3, patch of dimensions (27x27)mm2 and ground plane of dimensions (40x40)mm2 has been proposed with improved impedance bandwidth and gains for wireless communication applications.In this work, totally four types of antennas were designed and mentioned. Four types of antennas mean one is minkowski fractal antenna made by using microstrip patch and works at three different set of frequencies (8.17GHz, 9.20GHz & 15.32GHz) with high gain which mainly covers the applications of microwave frequency X-band and Ku band. Secondly, the combination of fractal and DGS that works at 11.5 GHz, which covers the applications of Ku band. The third design is DGS and works at dual set of frequencies (2.4 GHz & 5.25 GHz) and which mostly covers the major applications of WLAN, S-band frequency. Finally, the fourth design is plus shaped DGS works at multiple set of frequencies (13.73GHz ,15.50GHz,18.18GHz,21.04GHz) which mainly covers the major applications of K-band and Ku-band frequencies.